Interrogation/ police interview: Myth, realities and challenges (2018)
The police interview or interrogation, one of the major tools of criminal investigation is no longer confined to pre-trial investigations, but transcends to forensic labs and the Court rooms of learned Judges. The investigators, forensic experts and prosecutors need to act in synergy to improve the performance of the Criminal justice system. In this backdrop, the article examines the subject of interrogation on a broad canvass of constitutional and legal parameters, police professionalism and evidentiary value and human- civil rights issues. It underlines the need of the lead actors of the criminal justice system properly understanding certain myths and challenges connected with interrogation so that they can better appreciate the evidence or inputs generated through interrogation, at professional plane. It also discusses as how the science and technology have become a major aid in overcoming many bottlenecks in the traditionalmethods of interrogation or police interview.